P wave dispersion in patients with premenstrual dysphoric disorder - Yavuzkir, Seyda; Aydin, Suna; Baspinar, Melike; Korkmaz, Sevda; Deniz, Rulin; Baykus, Yakup; Yavuzkir, Mustafa (Journal of Cardiology and Cardiovascular Medicine, 2019)
Background: Growing evidence has revealed that fear and anxiety related situations could affect cardiac parameters. P wave dispersion (Pd) is an important index. In the present study, we aimed to evaluate Pd values in patients with premenstrual dysphoric disorder. Methods: The study was composed of twenty-five female patients with premenstrual dysphoric disorder and same number of healthy controls. Pd, Pmin and Pmax values were determined by electrocardiogram (ECG) in the subjects. Results: It was found that patients with premenstrual dysphoric disorder had considerably higher Pmax and Pmin values compared to those of healthy subjects. Pd was also significantly higher in patients with premenstrual dysphoric disorders than that of healthy subjects. Conclusion: Study suggests that patients with premenstrual dysphoric disorder seems to have increased Pd, as can be seen in anxiety and fear related clinical conditions, considering that this group of patients have an increased trend to cardiac abnormalities, particularly cardiac arrythmias. To access strong conclusion, it is required novel studies with larger samples.